Pengaruh Brand Trust Dan Persepsi Harga Terhadap Brand Loyalty Scarlett Whitening - Ihsan Awaludin (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
The purpose of this study was to examine the effect of brand trust and price perception on brand loyalty for Scarlett Whitening skin care products both partially and simultaneously. The survey method with a quantitative approach was used in this study by collecting data through a questionnaire. The population of this study amounted to 304 students with a sample of 77 students identified using simple random sampling technique with probability sampling approach. The results of hypothesis analysis testing using the help of SPSS 25 software show the results of the F test that brand trust and price perceptions simultaneously have a significant effect on brand loyalty. In addition, based on the results of the T test, it shows that brand trust and price perceptions partially affect brand loyalty.